Colorectal cancer-specific microbiome in peripheral circulation and cancer tissues - Yan, Shushan; Liu, Tie; Zhao, Haobin; Zhao, Chunbo; Zhu, Yuxin; Dai, Wenqing; Sun, Wenchang; Wang, Honggang; Sun, Junxi; Zhao, Lu; Xu, Donghua (Frontiers in Microbiology, 2024)
Introduction Accumulating evidence has supported that gut microbiota and metabolite profiles play indispensable roles in the pathogenesis of colorectal cancer (CRC), which ranks as the third most common cancer and the second leading cause of cancer-related deaths worldwide. However, alterations in tumoral or circulating microbiomes in CRC remain incompletely understood. It has been well-documented that tissue or serum microbiomes with low microbial biomass could be screened by use of 2bRAD sequencing for microbiome (2bRAD-M) at the species resolution. Methods In order to validate the microbial biomarkers distinguishing CRC and the variations in microorganisms present in serum and tumors, we performed 2bRAD-M to characterize the microbiomes in serum and cancer tissues of CRC patients with and without lymph node or liver metastasis. Results The composition of dominated microbiota in serum was different from that of tissue samples, while the microbial community composition of tumors was similar to that of the tumor-adjacent tissues. The analysis of α-diversity and β-diversity has revealed notable variations in serum microbiota diversities in CRC patients, particularly those with liver metastasis. Multiple CRC-specific microbial species, such as Moraxella A cinereus, Flavobacterium sp001800905, and Acinetobacter albensis, were identified in serum. Complicated functions and KEGG pathways were also confirmed in CRC according to the metastasis status. Discussion This study has found significant alterations in the microbial compositions and diversities in CRC and CRC-specific microbial species in both circulation and cancer tissues, which may serve as promising biomarkers for the screening, diagnosis and prognosis prediction of CRC. In particular, CRC-specific bacterial taxa are promising markers, holding transformative potentials in establishing personalized screening and risk stratification, refining much earlier non-invasive diagnostic approaches, and enhancing diagnostic sensitivity.